Having a toilet is not enough: the limitations in fulfilling the human rights to water and sanitation in a municipal school in Bahia, Brazil - Édila Dalmaso Coswosk; Priscila Neves-Silva; Celina Maria Modena; Léo Heller (BMC, 2019)
Abstract Background This article addresses the enjoyment of the human rights to water and sanitation (HRTWS), in particular access to toilets, in a public school in Bahia, Brazil. Methods Participant observation of the school's routine, focus groups with students in grades 8 and 9 of primary school (13 to 17 years old) and individual, semi-structured, interviews with members of school staff were applied, exploring access to water and sanitation by adolescent girls and boys. Results Students and school staff reported that the amount of toilets was insufficient and that their conditions were often inadequate because they were plugged or dirty. The impact on girls is greater as toilets do not offer a clean and healthy environment for menstrual hygiene management. Several elements of the normative content of the HRTWS, especially accessibility, acceptability, quality, safety and dignity, were largely not fulfilled. The study identified that, to comply with the HRTWS, it is necessary to go beyond infrastructure, as the lack of maintenance; cultural elements and student participation hinder the usage of sanitary facilities. Since schools can be privileged spaces to train critical and reflective citizens and to foster autonomy and emancipation, education oriented by human rights and citizenship is an opportunity for a more equitable society. By increasing access to social, economic and cultural rights in all phases and aspects of life, including when children and adolescents are in a school environment, people are able to enjoy better living conditions and a higher standard of health. Conclusions The study raised the importance of considering each community's sociocultural aspects in analyzing access to sanitary facilities in schools, which are spaces where citizens' rights should be exercised and fulfilled.